High prevalence of enterotoxigenic Escherichia coli strains in hospitalized diarrhea patients: a preliminary study from a cholera-endemic area in India (2022) - Khuntia, Hemant Kumar; Manna, Prabir; Barik, Deepak Kumar; Biswas, Subhojeet; Bramha, Prasanta Kumar; Pati, Sanghamitra; Ranjit, Manoranjan; Bal, Madhusmita; Kerketta, Anna Salomi (Frontiers in Microbiology, 2025)
IntroductionEnterotoxigenic Escherichia coli (ETEC), producing heat-stable (ST) and/or heat-labile (LT) enterotoxins, is a major cause of diarrhea in children and travelers in developing countries. Surveillance in cholera-endemic regions is crucial for timely public health response.MethodsBetween May and November 2022, a cross-sectional study was conducted in Puri, India. Rectal swabs from 256 hospitalized diarrhea patients were analyzed for diarrheagenic E. coli and Vibrio cholerae using microbiological and molecular methods. Antimicrobial susceptibility of ETEC isolates was also assessed.ResultsETEC was detected in 20.3% of cases, making it the most prevalent pathogen. No Vibrio cholerae was isolated. EAEC and EPEC were identified in 6.2% and 2.3% of cases, respectively. ETEC was significantly more common in children under 2 years (p < 0.00001), though overall age correlation was weak (R = –0.013). Symptoms included watery stool, vomiting, abdominal pain, and dehydration, with dehydration significantly associated with adults (p < 0.05). ETEC strains were susceptible to streptomycin, chloramphenicol, gentamicin, and amikacin.DiscussionETEC has emerged as the dominant diarrheal pathogen in a cholera-endemic area, posing a risk to both children and adults. These findings highlight the need for continued epidemiological monitoring and age-targeted interventions.